Reproducibility of the AO/ASIF and Gartland classifications for supracondylar fractures of the humerus in children - Igor Tadeu Silveira Rocha; André de Siqueira Faria; Carlos Fontoura Filho; Murilo Antônio Rocha (Revista Brasileira de Ortopedia, 2015)
OBJECTIVE: To evaluate the reproducibility of the radiographic classifications of Gartland and the Association for Osteosynthesis/Association for the Study of Internal Fixation (AO/ASIF) for supracondylar fractures of the humerus in children.METHODS: On two occasions, 50 radiographs in anteroposterior and lateral views were evaluated by three pediatric orthopedists in accordance with the Gartland and AO/ASIF pediatric classifications. Their responses were subjected to statistical analysis consisting of calculation of the κ coefficient to assess the intra- and interobserver concordance, in both classifications.RESULTS: The strength of the intraobserver concordance was high or near perfect for the three examiners in the two classification systems. The strength of the interobserver concordance was high in the two systems, with κcoefficients of 0.756 for the Gartland classification and 0.766 for the AO/ASIF classification.CONCLUSION: The Gartland and AO/ASIF classification systems showed similar reproducibility and performance. High strength of concordance was seen in the intra- and interobserver analyses.